The Role of AI in Green HRM: A Phenomenological Study on the Implementation of an Eco-friendly Chatbot for Sustainable Recruitment - Burhanuddin (Abadi Institute, 2025)
This phenomenological study examines the role of artificial intelligence (AI) in Green Human Resource Management (HRM), focusing on the implementation of eco-friendly chatbots for sustainable recruitment processes in Makassar, Indonesia. Through in-depth interviews with HR professionals, recruiters, and candidates, the research explores how AI-driven recruitment tools contribute to environmental sustainability by reducing paper waste, optimizing energy use, and enhancing green employer branding. While findings confirm significant efficiency gains and ecological benefits, they also reveal critical challenges, including algorithmic bias, digital inequity, and the risk of depersonalizing candidate experiences. The study highlights the need for ethical AI design, contextual implementation frameworks, and holistic sustainability strategies to ensure that technological advancements in HRM align with both environmental and social equity goals. By bridging the gap between AI innovation and sustainable HR practices, this research offers practical insights for organizations navigating the complexities of digital transformation in emerging economies.